Ovine neuronal ceroid lipofuscinosis: a large animal model syntenic with the human neuronal ceroid lipofuscinosis variant CLN6. Issue 9 (September 1998) - Broom, M F; Zhou, C; Broom, J E; Barwell, K J; Jolly, R D; Hill, D F
Abstract : The neuronal ceroid lipofuscinoses (NCLs) are a group of inherited degenerative neurological diseases affecting children. A number of non-allelic variants have been identified within the human population and the genes for some of these have recently been identified. The underlying mechanism for the neuropathology remains an enigma; however, pioneering studies with the naturally occurring ovine model (OCL) have led to the proposal that these diseases represent lesions in specific hydrophobic protein degradation pathways. In this study, we show linkage between OCL and microsatellite markers on OAR 7q13-15. Using interspecies chromosome painting we establish that OAR 7q13-15 is syntenic with human chromosome 15q21-23, the region which was recently defined as the location of a newly identified late infantile variant (CLN6). We propose that our ovine model represents a mutation in the gene orthologous to that mutated in the human late infantile variant CLN6. The ovine linkage flock, consisting of 56 families, represents a powerful resource for positional cloning of this NCL gene. The availability of such a large animal model will have important implications for experimentation in downstream corrective therapies.